Quantile regression: applications and current research areas - Yu, K.; Lu, Zudi; Stander, J. (Blackwell Publishing, 2009)
Quantile regression offers a more complete statistical model than mean regression and now has widespread applications. Consequently, we provide a review of this technique. We begin with an introduction to and motivation for quantile regression. We then discuss some typical application areas. Next we outline various approaches to estimation. We finish by briefly summarizing some recent research areas.